2000
DOI: 10.1007/s004210050671
|View full text |Cite
|
Sign up to set email alerts
|

An improved estimation of mean body temperature using combined direct calorimetry and thermometry

Abstract: The conventional method used to estimate the change in mean body temperature (dMBT) is by taking X% of a body core temperature and (1-X)% of weighted mean skin temperature, the value of X being dependent upon ambient temperature. This technique is used widely, despite opposition from calorimetrists. In the present paper we attempt to provide a better method. Minute-by-minute changes in dMBT, as assessed using calorimetry, and 21 (20 if esophageal temperature was unavailable) various regional temperatures (dRBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…However, the present study, with the exception of Snellen (38), is the first to use whole body direct air calorimetry to assess such a concept. Nadel et al (28) where T es is esophageal temperature; T m is quadriceps temperature, and T sk is mean skin temperature.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the present study, with the exception of Snellen (38), is the first to use whole body direct air calorimetry to assess such a concept. Nadel et al (28) where T es is esophageal temperature; T m is quadriceps temperature, and T sk is mean skin temperature.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research has shown that the two-compartmental thermometry model greatly underestimates ⌬T b and therefore ⌬H b (15,18,38,43). Despite this, the two-compartment model is still extensively used for the estimation of ⌬T b and ⌬H b , both as an analytical tool for assessing individual heat load status for a wide range of subpopulations (1,7,36,49) and extensively as a physiological criterion for maximal heat exposure (2,16,17,19,22).…”
mentioning
confidence: 99%
“…Modified from Kenny et al (2008) and used with permission. approach can result in significant underestimations of heat storage (Vallerand et al, 1992b;Snellen, 2000;Jay et al, 2007aJay et al, , 2007bSawka and Castellani, 2007). Comparisons using direct calorimetry showed those errors increased when moderate intensity exercise ( $ 40% maximal aerobic power) was performed in warmer conditions (i.e.…”
Section: Partitional Calorimetry Thermometry and Mean Body Temperaturementioning
confidence: 97%
“…Alternative coefficients have also been suggested for differing levels of clothing insulation (Aoyagi et al, 1996a(Aoyagi et al, , 1996b. However irrespective of the selected weighting coefficients several studies Horstman and Horvath, 1972;Snellen, 2000;Vallerand et al, 1992) have demonstrated that the two-compartmental thermometry model significantly underestimates DT ළ b and therefore DH b by up to ϳ35% (Jay et al, 2007). The thermometry approach is also limited to steady-state body temperatures both at rest and during exercise.…”
mentioning
confidence: 99%